Application of AHP Method for Failure Modes and Effect Analysis (FMEA) in Aerospace Industry for Aircraft Landing System - El Dandachi, Yahya El Osman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
FMEA has been used in the aerospace industry for many years; this industry has been growing rapidly, so reliability and safety guarantee have been of increasing concern within the aerospace industry. Conventional FMEA technique still imposes many common shortages in order to compute RPN, which is product of the Severity (S), Detection (D) and Occurrence (O). Conventional FMEA considers the important of the elements S, O and D with the same weight which is not effective in practical FMEA study. In our base article, the study was done by 4 experts using the fuzzy developed FMEA that yielded crisp RPN scores for the failure modes of the aircraft landing system used in the research, this imposes a problem when ranking the risks of those modes. In this study, we used AHP that helps decision makers find one that best suits their goal and their understanding of the problem. It provides a comprehensive and rational framework for structuring a decision problem, for representing and quantifying its elements, for relating those elements to overall goals, and for evaluating alternative solutions. When using the AHP method, expert‘s opinions and weights will be obtained and will be prioritized in a better way than FMEA weights. A pairwise comparison questionnaire was designed and distributed to 35 aerospace experts working in Jet Aviation, in Basel Switzerland, then critical selection factors were identified, consistency vector, index and rate were determined, ―expert choice 11.0‖ was applied to compute the outcomes. FMEA components were compared in the hierarchy, reaching the RPN and ranking its scores. RPN better values obtained showed the significant risk level attained by some FMs in the aircraft landing system that were used in our base study. Keywords: FMEA; AHP; Failure Mode; Risk Priority Number; Decision Making

ÖZ: FMEA, hava-uzay endüstrisinde yıllardır kullanılmaktadır; bu endüstri hızla büyümektedir, bu yüzden dayanıklılığı ve güven garantisi, hava-uzay endüstrisi ile yükseliĢe geçmiĢtir. Geleneksel FMEA tekniği, RPN hesadplamalarını bir çok sıkça rastlanan eksikliğiyle hala zorlamaktadır ki sonucu: Zorluk (Z), Tarama (T) and OluĢumu (O)‘dur. Geleneksel FMEA, Z, T ve O‘nun önemli elementlerini aynı ağırlıkla –ki bu, kullanıĢlı FMEA çalıĢmasını etkilemeyecek olan- birlikte göz önüne alır. Makalemizin temeli; bu çalıĢma belirsiz geliĢmiĢ olan FMEA‘yı kullanan 4 bilirkiĢi tarafından tamamlanmıĢtır ve bu araĢtırmada, uzay-hava iniĢ sistemi hata modlarının, hızlı RPN skorlarından yararlanılmıĢtır. Bu modların riskleri en yüksek mevkide problem yaratır. Bu çalıĢmada, amaçlarına en iyi uyan, karar yapıcıları bulmaya ve sorunları anlamaya yardımcı olan AHP‘yi kullandık. AHP, bir karar sorunu yapısı, elementleri temsil eden ve niceliğini belirleyen, bütün bu elementlerin amaçlarının tamamıyla iliĢkili olarak, etraflı ve mantıklı bir ana yapı iskeleti üretir. AHP yöntemi kullanıldığında, bilirkiĢinin düĢünceleri ve ağırlıkları elde edilecektir ve FMEA ağırlıklarına göre en iyi yönteme öncelik verilecektir. Bir, ikili kıyaslama anketi tasarladı ve Jet Havacılıkta, Basel-Ġsviçre‘de, çalıĢan 35 uzay-hava bilirkiĢisine dağıtıldı sonra kritik seçim faktörleri tanımlandı, uyumluluk vektörü, dizin ve değer belirlendi, ―bilirkiĢi seçimi 11.0‖ olarak sonuçların hesaplarına eklendi. FMEA bileĢenleri, bir düzen içerisinde karĢılaĢtırıldı, RPN‘ye ve skorların aĢamasına ulaĢıldı. RPN‘nin elde edilen daha iyi değerleri, hava-uzay iniĢ sistemlerinin bazı FM‘leri tarafından, önemli risk seviyelerine ulaĢıldığı gösterildi. Anahtar Kelimeler: FMEA; AHP; Hatalı Mod; Risk Öncelik Numarası; Karar Yapıcı
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2017. Supervisor: Assist. Prof. Dr. Sahand Daneshvar.
Keywords: Industrial Engineering; Quality control-Reliability (Engineering); Failure Mode; Risk Priority Number; Decision Making; FMEA; AHP